Módulos de Ulrich - Maia, Mariana de Brito (2013)
In this work, after the introduction of some concepts of Commutative Algebra, for instance dimension, minimal number of generators, and multiplicity, we prove the existence of a very special class of modules over Cohen-Macaulay rings, the so-called Ulrich modules. It is known that, if M is a maximal Cohen-Macaulay module over such ring, then (M) e(M). Our goal in this study is to prove the main cases where the equality (M) e(M) holds.